Lamina specific postnatal development of PKCγ interneurons within the rat medullary dorsal horn. Issue 1 (30th June 2016) - Mermet‐Joret, Noemie; Chatila, Nadwa; Pereira, Bruno; Monconduit, Lénaic; Dallel, Radhouane; Antri, Myriam
ABSTRACT: Protein kinase C gamma (PKCγ) interneurons, located in the superficial spinal (SDH) and medullary dorsal horns (MDH), have been shown to play a critical role in cutaneous mechanical hypersensitivity. However, a thorough characterization of their development in the MDH is lacking. Here, it is shown that the number of PKCγ‐ir interneurons changes from postnatal day 3 (P3) to P60 (adult) and such developmental changes differ according to laminae. PKCγ‐ir interneurons are already present at P3‐5 in laminae I, IIo, and III. In lamina III, they then decrease from P11–P15 to P60. Interestingly, PKCγ‐ir interneurons appear only at P6 in lamina IIi, and they conversely increase to reach adult levels at P11–15. Analysis of neurogenesis using bromodeoxyuridine (BrdU) does not detect any PKCγ‐BrdU double‐labeling in lamina IIi. Quantification of the neuronal marker, NeuN, reveals a sharp neuronal decline (∼50%) within all superficial MDH laminae during early development (P3–15), suggesting that developmental changes in PKCγ‐ir interneurons are independent from those of other neurons. Finally, neonatal capsaicin treatment, which produces a permanent loss of most unmyelinated afferent fibers, has no effect on the development of PKCγ‐ir interneurons. Together, the results show that: (i) the expression of PKCγ‐ir interneurons in MDH is developmentally regulated with a critical period at P11‐P15, (ii) PKCγ‐ir interneurons are developmentally heterogeneous, (iii) lamina IIi PKCγ‐ir interneurons appear less vulnerable to cell death, and (iv) postnatal maturation of PKCγ‐ir interneurons is due to neither neurogenesis, nor neuronal migration, and is independent of C‐fiber development. © 2016 Wiley Periodicals, Inc. Develop Neurobiol 77: 102–119, 2017